2008
DOI: 10.1021/ic701337u
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic and Spectroscopic Studies of Lanthanides(III) Complexation with Polyamines in Dimethyl Sulfoxide

Abstract: The thermodynamic parameters of complexation of Ln(III) cations with tris(2-aminoethyl)amine (tren) and tetraethylenepentamine (tetren) were determined in dimethyl sulfoxide (DMSO) by potentiometry and calorimetry. The excitation and emission spectra and luminescence decay constants of Eu3+ and Tb3+ complexed by tren and tetren, as well as those of the same lanthanides(III) complexed with diethylenetriamine (dien) and triethylenetetramine (trien), were also obtained in the same solvent. The combination of ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 43 publications
0
26
0
Order By: Relevance
“…However, according, to other studies, the thermodynamic aspects of lanthanide complexation with polyamides and ethylenediamine in dimethylsulfoxide, such as the trend in both DH 0 1 and DS 0 1 , indicated some changes in the average coordination number along the lanthanide series [17,39]. A similar irregularity was reported by Buenzli et al on the basis of FTIR studies of lanthanide trinitrates in the presence of DMSO in anhydrous acetonitrile [40].…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…However, according, to other studies, the thermodynamic aspects of lanthanide complexation with polyamides and ethylenediamine in dimethylsulfoxide, such as the trend in both DH 0 1 and DS 0 1 , indicated some changes in the average coordination number along the lanthanide series [17,39]. A similar irregularity was reported by Buenzli et al on the basis of FTIR studies of lanthanide trinitrates in the presence of DMSO in anhydrous acetonitrile [40].…”
Section: Discussionmentioning
confidence: 52%
“…Considerable efforts have been made to investigate the physicochemical properties of lanthanide complexes with polyamides and with halide ions [14,17,18]. However, data on solution densities and on the speed of sound in solutions of lanthanide ions are scarce and mainly limited to aqueous solutions [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…[36][37][38] As shown in Fig. 3, complexation of Ca 2+ and the tri-, penta-, and hexavalent f-elements by acetate follows such a linear trend when the value of the stability constant for the 1:1 complex is plotted as a function of effective cationic charge.…”
Section: Uo 2 (Gh 4 ) + Complex It Is Well Recognized That Solution mentioning
confidence: 84%
“…Recent thermodynamic and spectroscopic studies of tris-(2-aminoethyl) amine-lanthanide complexes 16 and the use of similar polyamine-CuBr complexes in polymerization reactions 17 show the significance of the tripod ligand. Very recently Chen et al demonstrated for the first time that 1,1,1-tris-(hydroxymethyl)ethane can be used as a O-donor tridentate-tripod ligand for Cu-catalyzed carbon-heteroatom bond formation.…”
Section: Introductionmentioning
confidence: 99%